2013
DOI: 10.1210/en.2013-1118
|View full text |Cite
|
Sign up to set email alerts
|

Carboxypeptidase E Protects Hippocampal Neurons During Stress in Male Mice by Up-regulating Pro-survival BCL2 Protein Expression

Abstract: Prolonged chronic stress causing elevated plasma glucocorticoids leads to neurodegeneration. Adaptation to stress (allostasis) through neuroprotective mechanisms can delay this process. Studies on hippocampal neurons have identified carboxypeptidase E (CPE) as a novel neuroprotective protein that acts extracellularly, independent of its enzymatic activity, although the mechanism of action is unclear. Here, we aim to determine if CPE plays a neuroprotective role in allostasis in mouse hippocampus during chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 36 publications
3
28
0
Order By: Relevance
“…CPE is secreted from (neuro)endocrine tumor and glioblastoma (GBM) cell lines., It was found that CPE acts as a pro-growth, but anti-metastatic factor [6]. Another recent study has shown that CPE acts extracellularly as a negative regulator of the canonical Wnt signaling pathway [13] and as a neurotrophic factor to protect neurons against oxidative stress induced cell death [9] or during chronic stress [14]. However, the mechanism of action of CPE in these functions is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…CPE is secreted from (neuro)endocrine tumor and glioblastoma (GBM) cell lines., It was found that CPE acts as a pro-growth, but anti-metastatic factor [6]. Another recent study has shown that CPE acts extracellularly as a negative regulator of the canonical Wnt signaling pathway [13] and as a neurotrophic factor to protect neurons against oxidative stress induced cell death [9] or during chronic stress [14]. However, the mechanism of action of CPE in these functions is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…) and after chronic restraint stress in mice (Murthy et al . ). In addition, CPE has recently been identified as a neuroprotective protein, now also known as neurotrophic factor‐α1 (henceforth referred to as NF‐α1 in this work), which is secreted from neurons and acts extra‐cellularly in an autocrine or paracrine manner (Woronowicz et al .…”
mentioning
confidence: 97%
“…17,8 CPE has also been implicated in cancer progression [18][19][20][21] and as a neuro-trophic factor regulating brain functions. [22][23][24][25][26] Lately, it was found that CPE is also involved in other biological processes such as bone homeostasis 27 and bowel disease. 28 We have previously shown that CPE negatively regulates the oncogenic canonical Wnt signaling pathway by interacting with Wnt3a leading to decreased β-catenin protein levels and reduced Wnt signaling levels.…”
Section: Discussionmentioning
confidence: 99%